2012
DOI: 10.1111/j.1468-2494.2012.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactobionic acid as antioxidant and moisturizing active in alkyl polyglucoside‐based topical emulsions: the colloidal structure, stability and efficacy evaluation

Abstract: Cosmeceutical antioxidants may protect the skin against oxidative injury, involved in the pathogenesis of many skin disorders. However, an unsuitable topical delivery system with compromising safety profile can affect the efficacy of an antioxidant active. This study investigated the antioxidant potential of lactobionic acid (LA), a newer cosmeceutical active, per se (in solution) and incorporated into natural alkyl polyglucoside (APG) emulsifier-based system using 1,1-diphenyl-2-picrylhydrazyl free radical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 34 publications
7
56
0
1
Order By: Relevance
“…This is because of the polyhydroxyl structural motif, resembling to a certain extent glycosaminoglycans. Taking into account that the physicochemical parameters of LA (molecular mass 358 g/mol and pKa = 3.8) and its structure are similar to those for glycolic acid [11]- [15], one may expect for LA some exfoliating properties.…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the polyhydroxyl structural motif, resembling to a certain extent glycosaminoglycans. Taking into account that the physicochemical parameters of LA (molecular mass 358 g/mol and pKa = 3.8) and its structure are similar to those for glycolic acid [11]- [15], one may expect for LA some exfoliating properties.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings have shown that lactobionic acid, as a highly hygroscopic substance, strongly influenced the colloidal structure of the emulsion based on APGs and even promoted the formation of lamellar structures thus influencing the mode of water distribution within the cream [154]. The investigation of glycolic acid efficacy confirmed that, when incorporated in an APG-based emulsion, this active shows less irritation [156]. Also, significantly improved skin moisturization and lack of skin irritation and damage, which are demonstrated in this study,a re explained with the effect of APG-based vehicle itself.…”
Section: A Lpha-hydroxy Acidsmentioning
confidence: 96%
“…It has created great interest among the food, pharmaceutical, chemical and cosmetics industries due to its functional properties (Gutiérrez et al 2012). The additive is approved by the US FDA (Food and Drug Administration) (FDA 2014) and has chelating, moisturizing and antioxidant properties (Isaacson et al 1989;Green et al 2009;Tasic-Kostov et al 2012).…”
Section: Introductionmentioning
confidence: 99%